The CD11a and Endothelial Protein C Receptor Marker Combination Simplifies and Improves the Purification of Mouse Hematopoietic Stem Cells. (15th March 2018) - Karimzadeh, Alborz; Scarfone, Vanessa M.; Varady, Erika; Chao, Connie; Grathwohl, Karin; Fathman, John W.; Fruman, David A.; Serwold, Thomas; Inlay, Matthew A.
Abstract : Hematopoietic stem cells (HSCs) are the self-renewing multipotent progenitors to all blood cell types. Identification and isolation of HSCs for study has depended on the expression of combinations of surface markers on HSCs that reliably distinguish them from other cell types. However, the increasing number of markers required to isolate HSCs has made it tedious, expensive, and difficult for newcomers, suggesting the need for a simpler panel of HSC markers. We previously showed that phenotypic HSCs could be separated based on expression of CD11a and that only the CD11a negative fraction contained true HSCs. Here, we show that CD11a and another HSC marker, endothelial protein C receptor (EPCR), can be used to effectively identify and purify HSCs. We introduce a new two-color HSC sorting method that can highly enrich for HSCs with efficiencies comparable to the gold standard combination of CD150 and CD48. Our results demonstrate that adding CD11a and EPCR to the HSC biologist's toolkit improves the purity of and simplifies isolation of HSCs.